KOMPARASI UPAYA ADMINISTRATIF PENYELESAIAN SENGKETA PROSES PEMILU DAN PEMILIHAN (Jurnal Huma Betang Demokrasi, 2021)
This article is intended to review important matters in the administrative legal remedies (administrative review) of local and general election process disputes, namely the subject of the dispute, the object of the dispute, the procedure and the legal force of the decision on the administrative review. The results of a comparative study found that the construction of the subject and object of the dispute is the same, the difference is only at the level of the nomenclature used, namely mediation and adjudication for electoral process disputes and open and closed deliberation for local election disputes. Regarding decisions, the decisions of Bawaslu, Provincial Bawaslu or Regency/City Bawaslu in disputes over the general election process are final and binding in three respects. First, decisions based on the results of the agreement. Second, the Bawaslu decision as referred to in Article 469 of the Election Law. Third, in the case of Bawaslu Decision, Provincial Bawaslu or Regency/City Bawaslu grants the applicant's request. Meanwhile, the decisions of the Provincial Bawaslu or Regency/City Bawaslu in local election disputes are final and binding in two respects. First, the decision is based on the results of the agreement. Second, the decision of the Provincial Bawaslu or Regency/City Bawaslu which grants the applicant's request.